Use of varenicline and nicotine replacement therapy in people with and without general practitioner-recorded dementia: retrospective cohort study of routine electronic medical records - Amy Taylor; Tim Jones; Taha Itani; Richard Martin; Gemma Taylor; Kyla Thomas; Neil Davies (BMJ Open)
Objectives Our primary objective was to estimate smoking prevalence and prescribing rates of varenicline and nicotine replacement therapy (NRT) in people with and without general practitioner (GP)-recorded dementia. Our secondary objective was to assess and compare quit rates of smokers with versus without GP-recorded dementia who were prescribed varenicline or NRT for smoking cessation.Design A retrospective cohort study based on the analysis of electronic medical records within the Clinical Practice Research Datalink (2007–2015).Setting 683 general practices in England.Participants People with and without GP-recorded dementia, aged 18 years and have a code indicating that they are a current smoker.Intervention Index prescription of varenicline or NRT (from 1 September 2006).Outcome measures The primary outcomes were smoking prevalence and prescribing rates of varenicline and NRT (2007–2015). The secondary outcome was smoking cessation at 2 years.Results Age and sex-standardised prevalence of smoking was slightly higher in people with GP-recorded dementia than in those without. There were 235 314 people aged 18 years and above prescribed NRT or varenicline. Among smokers with GP-recorded dementia (N=447), 409 were prescribed NRT and 38 varenicline. Smokers with GP-recorded dementia were 74% less likely (95% CI 64% to 82%) to be prescribed varenicline than NRT, compared with smokers without GP-recorded dementia. Compared with people without GP-recorded dementia, people with GP-recorded dementia had consistently lower prescribing rates of varenicline from 2007 to 2015. Two years after prescription, there was no clear evidence for a difference in the likelihood of smoking cessation after prescription of these medications between individuals with and without dementia (OR 1.0, 95% CI 0.8 to 1.2).Conclusions Between 2007 and 2015, people with GP-recorded dementia were less likely to be prescribed varenicline than those without dementia. Quit rates following prescription of either NRT or varenicline were similar in those with and without dementia.